Analysis of the Cochrane Review: Angiotensin Converging Enzyme Inhibitors Versus Angiotensin Receptor Blockers for Primary Hypertension. Cochrane Database Syst Rev. 2014,8: CD009096. - Nogueira-Silva, Luís (2015)
Angiotensin converting enzyme inhibitors and angiotensin receptor blockers are first line drugs in the treatment of hypertension. The aim of this review was to assess if there are differences between these drug classes regarding the prevention of total mortality, occurrence of cardiovascular events and of adverse effects. A systematic review and metanalysis was performed, searching for studies that compare angiotensin converting enzyme inhibitors and angiotensin receptor blockers face-to-face, in several databases until July 2014. The study selection and data extraction were performed by 2 independent researchers. Nine studies were included, with a total of 10 963 participants, 9 398 of which participated in the same study and had high cardiovascular risk. No differences were observed regarding total mortality, cardiovascular mortality or total cardiovascular events. A slightly smaller risk was observed with angiotensin receptor blockers regarding withdrawal due to adverse effects (55 people were needed to be treated with angiotensin receptor blockers for 4.1 years to avoid one withdrawal due to adverse effect), mainly due to the occurrence of dry cough with angiotensin converting enzyme inhibitors. Thus, no differences were observed between angiotensin converting enzyme inhibitors and angiotensin receptor blockers in the prevention of total mortality and cardiovascular events, and angiotensin receptor blockers were better tolerated. Given the large proportion of participants with a high cardiovascular risk, the generalization of these results to other populations is limited.